Dictionary of Arabic and allied loanwords : Spanish, Portuguese, Catalan, Galician and kindred dialects - Corriente, F. 1940- (Handbook of Oriental Studies. Section 1 The Near and Middle East, 2008)
One of the main cultural consequences of the contacts between Islam and the West has been the borrowing of hundreds of words, mostly of Arabic but also of other important languages of the Islamic world, such as Persian, Turkish, Berber, et cetera by Western languages. Such loanwords are particularly abundant and relevant in the case of the Iberian Peninsula because of the presence of Islamic states in it for many centuries; their study is very revealing when it comes to assess the impact of those states in the emergence and shaping of Western civilization. Some famous Arabic scholars, above all R. Dozy, have tackled this task in the past, followed by other attempts at increasing and improving his pioneering work; however, the progresses achieved during the last quarter of the 20th c., in such fields as Andalusi and Andalusi Romance dialectology and lexicology made it necessary to update all the available information on this topic and to offer it in English.